PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG SISWA KELAS V SD INPRES PANGGENGTUNGAN UTARA - Maulia, Dwi; Andi Mulawakkan Firdaus; Rezki Ramdani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of fifth-grade students on geometric shapes material, caused by abstract learning processes dominated by conventional methods. The purpose of this study is to determine the differences in learning outcomes and analyze the influence of implementing the Project Based Learning (PjBL) model on mathematics learning outcomes of fifth-grade students at SD Inpres Panggengtungan Utara. This study is a quantitative research using a quasi-experimental method with a Pretest-Posttest Control Group Design. The research population consisted of all fifth-grade students at SD Inpres Panggengtungan Utara, with samples divided into an experimental class (taught using the PjBL model) and a control class (taught using conventional methods). Data collection instruments included learning outcome tests (pretest and posttest), student activity observation sheets, and documentation. Data analysis techniques utilized descriptive statistics and inferential statistics (t-test) assisted by SPSS version 29. The results showed that the average posttest score of the experimental class (85.39) was higher than the control class (67.39). The learning completeness rate in the experimental class reached 83.3%, while the control class only reached 13.5%. The t-test results showed a Sig. (2-tailed) value of 0.001 < 0.05, indicating a significant difference in learning outcomes. The increase in learning outcomes in the experimental class was categorized as high with an average N-Gain value of 0.72. Thus, it can be concluded that the Project Based Learning model significantly influences the improvement of students' mathematics learning outcomes on geometric shapes material. Keywords: Project Based Learning, Learning Outcomes, Mathematics, Geometric Shapes